Evaluation of coronary microvascular dysfunction using magnetocardiography: A new application to an old technology - Namrita Ashokprabhu; Khaled Ziada; Edouard Daher; Leslie Cho; Christian W. Schmidt; Yulith Roca; Cassady Palmer; Sukhleen Kaur; Timothy D. Henry; Carl J. Pepine; Odayme Quesada (American Heart Journal Plus, 2024)
Background: In patients with angina and non-obstructive coronary artery disease (ANOCA), diagnosis of coronary microvascular dysfunction (CMD) remains an unmet need. Magnetocardiography (MCG), is a rest-based, non-invasive scan that can detect weak electrophysiological changes that occur at the early phase of ischemia. Objective: This study assessed the ability of MCG to detect CMD in ANOCA patients as compared to reference standard, invasive coronary flow reserve (CFR). Methods: Patients with ANOCA and invasive coronary physiologic assessment using intracoronary flow measurements with Doppler and thermodilution methods were enrolled. CMD was defined dichotomously as an invasive CFR < 2.0 by Doppler or thermodilution assessment. Noninvasive 36-channel 90-s MCG scan was performed and quantitative assessment of four distinct MCG features was completed. We evaluated the diagnostic performance of 2 or more abnormal MCG features to detect CMD in the overall cohort and performed a subgroup analysis in the subset of patients with Doppler CFR assessment. Results: Among 79 ANOCA patients, 25 were CMD positive and 54 patients were CMD negative by CFR. Using invasive CFR as reference, MCG had an ROC AUC of 0.66 with a sensitivity of 68 % and specificity of 65 % for the detection of CMD. In the subgroup with Doppler CFR assessment, MCG had an ROC AUC of 0.76 with a sensitivity of 75 % and specificity of 77 %. Conclusions: In ANOCA patients, MCG demonstrates the ability to detect CMD using a 90-second non-invasive scan without the need for an intravenous stressor or ionizing radiation. Further investigations are needed to validate an MCG-based diagnostic pathway for CMD.